OPTIMASI PERENCANAAN PENGGUNAAN LAHAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFI (SIG) DAN SOIL AND WATER ASSESSMENT TOOL (SWAT) (SUATU STUDI DI DAS CIJALUPANG, BANDUNG, JAWA BARAT) - Erna Suryani; Suria Darma Tarigan (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
The use and management of land resource which are unsuitable with its land capability will cause physical, chemical and biological-damage to the land and will disturb its hydro-orological function. The damage of land resources in a watershed needs improvement to increase its land quality. Optimal land use management planning based on its land suitability and hydrological aspects become important and need to be applied. The objectives of the study were: 1) To analyze land use change at Cijalupang Watershed, 2) To evaluate SWAT capability to predict impact of land use change on the hydrologic characteritics of the watershed, and 3) To provide land use plan based on land quality and hydrologic characteritics of the watershed. The result showed that optimizing land use management by integrating GIS and SWAT model at the Cijalupang Watershed was capable to increase land quality of the watershed. This was shown by the improvement of its land use capability to create better hydrological condition by decreasing run off 2.1 % and increasing base flow and lateral flow 0.4% and 0.4% respectively.